Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*36.14px); top: calc(var(–scale-factor)*126.52px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.987259);" role="presentation">Dear colleagues, <span dir="ltr" style="left: calc(var(–scale-factor)*36.14px); top: calc(var(–scale-factor)*154.87px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.996185);" role="presentation">Recently, on November 14, 2023, the results of the Third Grushin’s Book Award were announced. A festive <span dir="ltr" style="left: calc(var(–scale-factor)*36.14px); top: calc(var(–scale-factor)*169.04px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.970668);" role="presentation">ceremony praising the winners took place at the Moscow School of Social and Economic Sciences (Shaninka). <span dir="ltr" style="left: calc(var(–scale-factor)*36.14px); top: calc(var(–scale-factor)*183.22px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.984775);" role="presentation">We are proud to inform you that a major award went to the book <span dir="ltr" style="left: calc(var(–scale-factor)*348.78px); top: calc(var(–scale-factor)*183.22px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.979335);" role="presentation">What Do We Know About Freelancers? The <span dir="ltr" style="left: calc(var(–scale-factor)*36.14px); top: calc(var(–scale-factor)*197.39px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.962416);" role="presentation">Sociology of Free Employment <span dir="ltr" style="left: calc(var(–scale-factor)*186.19px); top: calc(var(–scale-factor)*197.39px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.985458);" role="presentation">(Moscow: HSE Publishing House, 2022) written by our colleagues doing eco<span dir="ltr" style="left: calc(var(–scale-factor)*36.14px); top: calc(var(–scale-factor)*211.56px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(1.00076);" role="presentation">nomic sociology Denis Strebkov and Andrey Shevchuk (both from the LSES, HSE University). Our sincere <span dir="ltr" style="left: calc(var(–scale-factor)*36.14px); top: calc(var(–scale-factor)*225.74px); font-size: calc(var(–scale-factor)*12.00px); font-family: serif; transform: scaleX(0.98263);" role="presentation">congratulations to the win!